Further education or re-enlistment decision in Turkish armed forces: A seemingly unrelated probit analysis - Yıldırım, Juelide; Karasu, Şemsettin; GÜMÜŞOĞLU, NEBİLE KORUCU (Taylor & Francis Ltd, 4 Park Square, Milton Park, Abingdon Ox14 4Rn, Oxon, England, 2010)
Previous empirical studies examining the determinants of re-enlistment probabilities have generally employed a univariate approach and have suggested that expected further education increases the likelihood of joining the army. However, the re-enlistment and further education decisions can be interdependent. Accordingly, this study employs a seemingly unrelated bivariate probit model to jointly estimate the factors that influence both further education and re-enlistment decisions. Empirical analysis indicates that there is a correlation between the re-enlistment and further education decisions, revealing that previous single equation models might be misspecified. Moreover the geographical background, education level of the conscript, intention of further education and previous unemployment duration are influential in the re-enlistment decision. Additionally, the further education decision appears to be determined by family and sibship characteristics, education level and age.
Keywords: Re-enlistment; Further education; Turkish Armed Forces; Seemingly unrelated probit; Personnel Supply Model; All-Volunteer Force; 1St-Term; Males